Is It About Who You Know? The Role of Social Capital on Re-employability of Older Women in Urban China - Yang, Yang Kan; Omar, Noralina; Siti Hajar, Abu Bakar Ah (Journal of Ecohumanism, 2024)
Evidence concerning the impact of the social capital of older women on labor market outcomes is complex. This article aims to examine and demonstrate the effect of social capital on the re-employability of older retired women in urban China and to reveal the process of accessing their re-employment position via social capital. This paper seizes data from a self-reported survey conducted in four major cities of Fujian province in China among women who are fully retired or re-employed and aged from 55 to 75. The results show that social capital is still the principal method for older women to access the workforce post-retirement. Individuals’ weak ties significantly improve the re-employment possibilities of older retired women. However, the results also indicate that using social capital, especially blood capital, as solid ties do not ensure the quality of re-employment for older women, which means the benefits, wages, and labor rights of re-employment jobs are not guaranteed.